Scientific Horizon: Basis for Developing Basic Mathematics Teaching Materials - Kusaeri, Al; Pardi, Habib Husnial; Evendi, Erpin (IKIP Mataram, 2024)
This study explores the development and validation of mathematics teaching materials that integrate Islamic values to foster both cognitive and ethical growth in students. Utilizing the scientific horizon model, these materials were designed to connect mathematical concepts with Islamic teachings, making learning relevant to students’ cultural and spiritual backgrounds. The development followed the Plomp model, with five stages: initial investigation, design, development, evaluation, and dissemination. Expert validation rated the materials as